PERMAINAN EDUKATIF UNTUK MENINGKATKAN PENGETAHUAN TENTANG KEBERSIHAN KUKU DI TK DHARMA WANITA PERSATUAN I SUMBERSEKAR - Yulinda Cesa, Fibe; Yuliati, Leny; Setya Dhini, Ellyvina; Tamara, Aulia; Cinta Sari, Yunda; B. Maharani, Novia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Personal hygiene, especially nail hygiene, is a basic need that should be cultivated from an early age. Neglecting this can lead to a decline in awareness of personal hygiene and increase the risk of infectious diseases later in life. Kindergarten students, aged 4-5 years, are not fully aware of this. The methods employed include socialization; initial discussion and situational analysis; material preparation; questionnaire validity and reliability testing; socialization of the activity plan; activity implementation; monitoring and evaluation, and discussion. In this case, the educational module includes instructional materials, educational games as visual aids, and mini experiments. The counseling activity was conducted by providing instructional materials on proper handwashing followed by a mini handwashing experiment. After this activity, it continued with an educational material on nail cutting and its experiment. Based on the average student scores before and after the counseling, there was an increase in the average student score from 66 to 80 (p-value = 0.002*). Thus, this counseling has a significant impact on increasing students' knowledge and average scores.